Basal and Infectious Enteritis in Broilers Under the I See Inside Methodology: A Chronological Evaluation - Sanches, Adrien W. D.; Belote, Bruna L.; Hümmelgen, Paulo; Heemann, Ana C. W.; Soares, Igor; Tujimoto-Silva, Aline; Tirado, Amanda G. C.; Cunha, Anderson F.; Santin, Elizabeth (Frontiers in Veterinary Science, 2020)
Recently, the inflammation of the intestinal mucosa has been related to many diseases in humans and animals. The concept of Microscopic Enteritis (ME) used in human pathology through the Marsh classification system has no counter-part in veterinary medicine. In poultry science, the I See Inside (ISI) methodology, unlike the current linear measures of villi and crypts, generates possibilities to describe and understand the avian ME. Through specific parameters, graded from 0 to 3, the model links proliferative and/or inflammatory reactions in the intestinal layers to some loss in performance. Herein, two trials were conducted in order to describe the development of ME through the ISI methodology in chickens challenged or not with Eimeria spp. and Clostridium perfringens. In each trial, a total of 64 birds were divided in 2 treatments with 4 replicates containing 8 birds each: non-challenged (NCH) and challenged (CH) through gavage with an Eimeria spp vaccine at 1 day of age and 108 CFU/mL of Clostridium perfringens administered at 10, 11, and 12 days of age. At 7, 14, 21 and 28 days of age birds were euthanized and samples of ileum and liver were collected for ISI evaluation, cytokines and presence of macrophages, CD4+ and CD8+ cell. The results allowed the description of the avian Microscopic Enteritis and of its two basic components: a basal enteritis (BE) in NCH broilers, over which the infectious enteritis is developed in CH birds. In addition, the chronology of ME translated by the ISI methodology parameters were associated to losses in zootechnical performance.